Royal visits - Prince Charles. ([Australia] : [publisher not identified], 1965)
Includes articles from the period 1965 to 1985 on visits to Australia by Prince Charles, many from 1966 when he attended Timber Tops, and visits with Princess Diana in 1983 and 1985. There are also articles on visits in 1974, 1977, 1979 and 1981.
Keywords: Charles, -- Prince of Wales, -- 1948- -- Travel -- Australia; Diana -- Princess of Wales, -- 1961-1997 -- Travel -- Australia; Royal visitors -- Australia; Visits of state -- Australia; Royal visits z Australia; Australian